Budgetary Participation's Effect on Managerial Outcomes: Mediating Roles of Self-efficacy and Attitudes toward Budgetary Decision Makers - 倪豐裕(Ni, Feng-yu); 蘇錦俊(Su, Chin-chun); 鍾紹熙(Chung, Shao-hsi); 鄭國枝(Cheng, Kuo-chih) (Tai Da Guan Li Lun Cong, 2009)
This study employs social-cognitive and affective events theories to examine the mediating roles of attitudes toward budgetary decision makers and self-efficacy between budgetary participation and managerial outcomes. The relationships between mediating variables and between managerial outcomes were also examined in this study. Structural equation modeling (SEM) was used to test the theoretical model with 164 useful responses which was randomly drawn from the listing companies in Taiwan Stock Exchange. The results show that the indirect effects of budgetary participation on managerial outcomes through self-efficacy and attitudes are supported. Self-efficacy also plays the mediating role between budgetary participation and attitudes. Implications and directions for future research are discussed.